Analisa Cost and Revenue Hubungannya dengan Profit Margin Hasil Pertanian Sayuran Kacang Panjang dan Mantimun pada Usaha Pertanian Sayuran Mandiri Kelurahan Jembatan Mas Kecamtan Pemayung Kabupaten Batang Hari - Akhmadi Akhmadi (Universitas Batanghari Jambi, 2021)
Cost and Revenue analysis in this study is intended to examine the details of costs (costs) that must be incurred by farmers, starting from preparation for one planting season to the marketed vegetable production for two types of vegetable crops, namely Long Beans and Cucumber The details of the costs referred to will be grouped into Fixed Costs (FC) and Variable Costs (VC), then the amount of costs incurred for one park season will be obtained with the Formulation TC = FC + VC. Furthermore, from the production results of the two types of vegetable crops, Total Revenue (TR) will be calculated through the formulation TR = QXP where TR is the Total Revenue obtained from the cumulative production results for each Harvest season (Q) multiplied by the price level at each sale of each product. harvest season (P). From the Total Revenue obtained each planting season, if all costs and other obligations are deducted, it can be seen that the Net Profit for the two types of vegetable crops in question. If the calculation results between Total Cost and Total Revenue have been obtained, then the Profit Margin of each type of vegetable crop will be analyzed between Long Beans and Cucumbers by dividing the net profit (Net Profit) by the sales proceeds (TR). From this calculation, it will be obtained the results of the comparative analysis of the profit margin of the Kancang Panjang farming business with cucumber as a consideration for farmers in opening a business.